WOMEN'S ROLE IN FINANCIAL REPORTING OF MICRO, SMALL, AND MEDIUM ENTERPRISES: A DECADE-LONG CASE STUDY IN MATARAM CITY (2014–2024) - Yunia Ulfa Variana; Rahmat Akbar Kurniawan (Universitas Islam Negeri Mataram, 2026)
This study investigates the role of women entrepreneurs in financial reporting practices among Micro, Small, and Medium Enterprises (MSMEs) in Mataram City, West Nusa Tenggara Province, Indonesia, over a ten-year period from 2014 to 2024. Grounded in Stewardship Theory (Donaldson & Davis, 1991) and augmented by Islamic financial ethics, this research employs a descriptive qualitative approach supplemented by longitudinal secondary data obtained from the Central Bureau of Statistics (BPS) of Mataram City and the Mataram City Cooperative and SME Office. The study systematically examines three dimensions: (1) the quantitative growth trajectory of women-led MSMEs across the decade, (2) the comparative quality of financial reporting between women- and men-managed enterprises, and (3) the mediating influence of local socio-cultural values—particularly the Sasak concept of 'amanah' (trustworthiness)—on financial accountability behavior. Findings reveal a statistically significant increase of 45% in women's formal participation in the MSME sector, with women-managed enterprises demonstrating superior consistency in daily transaction recording, budget separation, and cash flow management. However, a persistent digital financial literacy gap impedes full adoption of government-mandated accounting tools such as SI APIK. The study concludes that culturally embedded stewardship values substantially reinforce women's financial discipline, representing an underexplored nexus between Islamic moral economy and SME governance. Practical implications are proposed for local government policy on gendered financial literacy interventions. Kata kunci: Women Entrepreneurs; Financial Reporting; MSMEs; Stewardship Theory; Mataram City; Islamic Business Ethics; Digital Financial Literacy; Gender and Accounting